Do high-performance Employee influenced Work Motivation and Compensation in a Corporations? - Hakim, Adi Lukman; Faizah, Erna Nur (Publisher Cv. Inara, 2023)
Companies depend more on their workforce than just suitable facilities and advanced equipment to achieve their goals. To achieve organizational goals, human resources - particularly employees - play an important role. This study aims to explain how the relationship between work motivation, compensation, and employee performance; how these factors affect employee performance; and which component has the most influence on employee performance. A total of 35 employees were involved in this study. The method used was the total sampling method. To collect information, surveys and interviews were conducted. Scale range and multiple linear regression were used as analytical techniques to assess and validate the research hypotheses. Employee performance has a positive impact on the company. The same results also show that work motivation and compensation have an effect on the success of the company, employee performance increases when incentives and work motivation are improved. This implies that work motivation and compensation have a positive influence on employee performance.